QUEER (RE)VISIONS OF ARCHIVE, AFFECT, AND PLACE IN CHILD AND YOUTH CARE - A., August (International Journal of Child, Youth and Family Studies, 2021)
This article presents an autoethnography that interweaves the queering of archive, affect, and place using an object-oriented method. Engaging with a hundred-year-old antique photo album found in a thrift store, this article brings forth queer (re)visions of past, present, and future that (re)imagine queer (be)longing, which expand spheres of ancestral consciousness in 2SLGBTQIAA+ communities. Situated in the United States, this work traces the entanglements in this object-oriented autoethnography through a mapping of queer identity in the Pacific Northwest, capturing temporal reflections that reach from the present back into 1918 and back further still into the early English colonies. In orienting towards the realm of queering child and youth care this work seeks to contribute to a cultivation of discourse of collective (re)visions of past, present, and future that uproots the enshrined settler-colonial, white supremacist, heteropatriarchal, capitalist ethos that continuously crafts the layered erasures of sex, gender, and sexually diverse people in the United States. I endeavour in the threading of autoethnography, both as a white settler and in my being and continually becoming, a genderqueer, trans person struggling and thriving, to critically query the implications of this history within the present and to (re)affirm the possibilities for queer and trans youth in the future.